(untitled) (Indian Journal of Arid Horticulture, 2025)
Date palm (Phoenix dactylifera Linn.) is an impor- tant arid fruit plant. Datepalm fruits have high nutritive value as it has high calorific value 60-65 per cent sugar (3150 calories/ kg of fresh fruits) and fair amount of fibre (2.5%), protein (2.0%), fat (upto 2.0%) and minerals (upto 2.0%) Pectic substances (less than 2.0%) and vitamins (Vitamin A, Vitamin B, and Vitamin B,). The date palm tree. plantation in arid regions of Rajasthan can improve the ecology of the arid region by providing green cover to the barren land and by improving the micro climate of the re- gion.